Neck spasm after chemoradiotherapy for head and neck cancer: Natural history and dosimetric correlates. Issue 2 (4th April 2013) - Hunter, Klaudia U.; Worden, Francis; Bradford, Carol; Prince, Mark; McLean, Scott; Wolf, Gregory; Chepeha, Douglas B.; Eisbruch, Avraham
<x xml:space="preserve">Abstract</x> Background Little is known about the determinants of postradiation neck spasms in patients with head and neck cancer. Methods Patients with head and neck cancer treated with radiation therapy (RT) from 2004 to 2010 who experienced neck spasms werereviewed. Radiation doses were generated for their sternocleidomastoid (SCM) muscles bilaterally. Unaffected SCMs were used as controls. Results Thirty‐four patients reported neck spasms. Thirty had received definitive chemoradiation, and 4 had RT alone. Seven also had an ipsilateral neck dissection. Median time to onset was 23 months (range, 6–67 months). There were significantly higher radiation doses to the affected SCMs with a median of the mean dose to the affected and unaffected SCM of 62.3 Gy (range, 29–71 Gy) and 53.7 Gy (range, 27–65 Gy), respectively (p < .0001). Other dosimetric variables were also statistically significant but were highly correlated with the mean SCM dose. Neck dissection did not affect our results. Conclusion Neck spasms after chemotherapy intensity‐modulated radiation therapy (IMRT) shows a strong dose–response relationship. © 2013 Wiley Periodicals, Inc. Head Neck 36: 176–180, 2014